Learning to Communicate and Solve Visual Blocks-World Tasks - Zhang, Qi; Lewis, Richard; Singh, Satinder; Durfee, Edmund (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We study emergent communication between speaker and listener recurrent neural-network agents that are tasked to cooperatively construct a blocks-world target image sampled from a generative grammar of blocks configurations. The speaker receives the target image and learns to emit a sequence of discrete symbols from a fixed vocabulary. The listener learns to construct a blocks-world image by choosing block placement actions as a function of the speaker’s full utterance and the image of the ongoing construction. Our contributions are (a) the introduction of a task domain for studying emergent communication that is both challenging and affords useful analyses of the emergent protocols; (b) an empirical comparison of the interpolation and extrapolation performance of training via supervised, (contextual) Bandit, and reinforcement learning; and (c) evidence for the emergence of interesting linguistic properties in the RL agent protocol that are distinct from the other two.